セールロンダーネ サンチ ニ オケル セイブツ チョウサ - 大山, 佳邦; オオヤマ, ヨシクニ; 東, 正剛; ヒガシ, セイゴ; 宮脇, 博己; ミヤワキ, ヒロミ; 蛭田, 真一; ヒルタ, シンイチ; 神田, 啓史; カンダ, ヒロシ; Ohyama, Yoshikuni; Higashi, Seigo; et al. (1991)
P(論文) 第27-31次南極地域観測隊(1986-1990)において, 「陸上生態系構造の研究」計画を実施した。これは国際的なBIOTAS計画に関連した研究計画であった。第27-29次観測隊では越冬観測により, 昭和基地周辺の沿岸露岩域, 特にラングホブデ雪鳥沢の生態系を調査し, 第30-31次観測隊は夏隊によりセールロンダーネ山地の内陸露岩域における生物調査を実施した。前者についてはすでに報告されているので, ここでは後者について報告する。第30次観測隊には2名の隊員が参加し, 陸上のルートをたどり, 同山地の西部露岩域において土壌動物および地衣類を中心とした調査を行った。また第31次観測隊は1名の隊員のみであったが, ヘリコプターを夏季オペレーションに導入したことにより, 同山地を広く調査することができた。前次隊同様, 土壌動物を中心に調査し, 植物の採取にも努めた。詳細な研究は今後にまつが, 地衣類や節足動物に新たな知見がもたらされている。 From 1986 to 1990,a survey of terrestrial biology was carried out as one of the main projects of the Japanese Antarctic Research Expedition, corresponding to the international BIOTAS program. The terrestrial ecology was studied by wintering personnel during the first three years. For this research the SSSI of the Yukidori Valley was used as a main research field. Since the main research activities at that time were already reported by H. KANDA et al. (Nankyoku Shiryo, 34,76,1990), the present report deals with the research activities conducted in the Sør Rondane Mountains, Dronning Maud Land, during the last two summer seasons. The 1989 survey was made in the western part of the Mountains by means of snow vehicles, and the 1990 survey covered the entire area of the Mountains by using helicopters. Lichens were widely distributed in the Mountains, but well-developed communities of mosses and algae were restricted to the western part of the Mountains. One springtail and several mite species were also found in these western areas and Mefjell which is located in the central part of the Mountains. departmental bulletin paper